Effect of W-Mo doping on the phase transition temperature of VO2 synthesized by hydrothermal microwave method. (1st March 2023) - Liu, Yan; Jiang, Tienan; Lv, Yang; Zhou, Xinyu; Zhu, Henan; Shen, Qihui
Abstract: In this study, the combination of hydrothermal microwave technology and high-temperature method was used to efficiently control the formation of M-phase vanadium dioxide (VO2 ) nanoparticles, which were promising materials for optoelectronic switches and smart windows due to their excellent optoelectronic properties during the phase transition. The phase state and structure of VO2 depended on its synthesis parameters, and the results showed that the optimal conditions for VO2 (B) synthesis in a hydrothermal microwave were 120 °C for 2 h, which was a novel method for efficiently preparing VO2 (B) at a low temperature. By vacuum annealing, VO2 (B) could be transformed into monoclinic VO2 (R), where VO2 (R) converts into VO2 (M) on cooling to room temperature. Furthermore, the phase transition temperature of W-Mo co-doped VO2 (M) decreased by 14.8 °C, showing that the incorporation of W-Mo elements into the VO2 -based structure affects the material's phase transition temperature.